Management and administration of dental health services - Montalvo Núñez, Katherine Alessandra (2021)
Within medical informatics there’s dental informatics, which deals with the management of information, communication, and the application of new technologies in clinical practice and research. These computer systems involve the storage of information and will be in charge of organizing the work in the dental clinic.(Specified, 2009) Objective: The primary objective of this research work is to know the need to manage and administer dental health services through computer systems in the city of Chiclayo. Method: It is a cross-sectional, descriptive, observational, and prospective study. Which comprised conducting questionnaires to the owners of dental clinics, administrative personnel, dentists, and patients who attend the different dental clinics that are in the City of Chiclayo. Results: We verified that there were contrasting hypotheses. Conclusions: We conclude that there is a need to implement dental clinics with computer systems.